Study of the hydrogen production by the aqueous phase reforming of glycerol over Ni-based catalysts - Raso Roka, Raquel; Abad, Eduardo; García, Lucía; Ruiz, Joaquín; Oliva, Miriam; Arauzo, Jesús (Jornada de Jóvenes Investigadores del I3A, 2022)
The present work studied the effects of loading Fe, Ca, and the impurities of glycerol on the Ni/Al catalytic behavior in the aqueous phase reforming (APR) of glycerol to obtain renewable hydrogen.